(untitled) (Journal of Business and Technology (Dhaka), 2012)
People are always concerned about the improvement of their standard of living. In respect of this awareness, financial institutions of Bangladesh specially banking sectors are trying to expand their service net. And in this regard banking sector is playing a tremendous role through Retail Banking (RB). Toward the community development, RB has further enlarged its’ position as a major channel of business. RB has taken the foremost funding responsibility as well as commitment to give fast forwarding service to the community through increasing branche, alternative delivery channels, premier banking services. In this study the authors have selected 28 listed banks which covered 59.57% of listed financial institutions in stock exchange. The study has revealed that during the period of 2006-2008 the sample banks have offered different types of retail products (deposits increased by 88.18%, loan products increased by 48.50%, and cards service by 21.15%) by increasing number of branches by 19.28%.The authors have segmented the article into four parts Firstly an overview of RB, secondly, review of previous studies done in this area, thirdly a comparative analysis of data and its findings and finally conclusive remarks and policy implications. Keywords: Retail banking, Deposit Scheme, Loan, Card service, Delivery channels. DOI: http://dx.doi.org/10.3329/jbt.v5i2.9988 Journal of Technology (Dhaka) Vol. 5(2), July-December, 2010 166-179